2009
DOI: 10.2139/ssrn.1407574
|View full text |Cite
|
Sign up to set email alerts
|

A Consistent Model of 'Explosive' Financial Bubbles with Mean-Reversing Residuals

Abstract: We present a self-consistent model for explosive financial bubbles, which combines a mean-reverting volatility process and a stochastic conditional return which reflects nonlinear positive feedbacks and continuous updates of the investors' beliefs and sentiments. The conditional expected returns exhibit faster-than-exponential acceleration decorated by accelerating oscillations, called "log-periodic power law." Tests on residuals show a remarkable low rate (0.2%) of false positives when applied to a GARCH benc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The associated eigenvectors confirm the wisdom that the stiffer a direction, the more likely that it is close to an axis, and yWhile the beginning of a bubble is supposed to be given by the lowest value since the previous crash, it may be moved from this minimum to some later date; in Johansen and Sornette (2001) the beginnings of half of the eight bubbles on the Hang Seng up to 1998 were thus moved (Bre´e and Joseph 2010). zLomb periodograms ( van Bothmer 2003) or the residuals (Gazola et al 2008, Lin et al 2009) have been proposed, with mixed results. reversely for sloppy eigenvalues (Gutenkunst et al 2007).…”
Section: Sloppinessmentioning
confidence: 99%
See 2 more Smart Citations
“…The associated eigenvectors confirm the wisdom that the stiffer a direction, the more likely that it is close to an axis, and yWhile the beginning of a bubble is supposed to be given by the lowest value since the previous crash, it may be moved from this minimum to some later date; in Johansen and Sornette (2001) the beginnings of half of the eight bubbles on the Hang Seng up to 1998 were thus moved (Bre´e and Joseph 2010). zLomb periodograms ( van Bothmer 2003) or the residuals (Gazola et al 2008, Lin et al 2009) have been proposed, with mixed results. reversely for sloppy eigenvalues (Gutenkunst et al 2007).…”
Section: Sloppinessmentioning
confidence: 99%
“…Of the recent progress, the residuals have been shown to be AR(1) (Gazola et al 2008, Lin et al 2009). It makes sense, therefore, to create artificial data with AR(1) noise.…”
Section: Fitting Full Log-periodic Functions With Ar(1) Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Johansen and Sornette [31] have found that two-thirds of the dragon-kings identified in the distribution of drawdowns are actually stock market crashes, which were preceded by large bubbles. This has led them to build a theory [33][34][35] in which crashes are seen as the possible end of a bubble regime, associated with various positive feedback mechanisms that lead to faster-than-exponential unsustainable growth regime. The mechanisms responsible for positive feedbacks include portfolio insurance trading, option hedging, momentum investment and imitation-based herding.…”
Section: Dragon-kings In the Distribution Of Financial Drawdowns (Or mentioning
confidence: 99%
“…At the time of writing, the last one on the Shanghai market is still running. It is important to stress that our methodology allows us to predict the end of bubbles, but not the crashes per se [33][34][35]. It is often the case that a bubble bursts into a crash but this is not always the case.…”
Section: Prediction Of the End Of Financial Bubblesmentioning
confidence: 99%